Regency Hospital Limited (B) : the road travelled - Gupta, Parvinder (SAGE Knowledge. Cases., 2017)
A lot had changed at Regency Hospital Limited (RHL) by December 2009 when the case writers visited it after almost nine years. The founder Dr. Atul Kapoor was looking younger and rejuvenated! A sense of enthusiasm was evident all around. RHL had finally become debt free and was making profits. Dr. Kapoors focus was now on initiating and finalizing some of the expansion plans at RHL.